PENGARUH PEMBERIAN PUPUK ORGANIK CAIR DAUN GAMAL (Gliricidia sepium (Jacq.) Kunth ex Walp.) TERHADAP PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) - Fitri Oviyanti; Syarifah Syarifah; Nurul Hidayah (Biota, 2016)
Gamal (Gliricidia sepium (Jacq.) Kunth ex Walp.) is a plant leguminoceae class. So far, only gliricidia plants used as feed for ruminants, even though this plant has the potential as a source of nutrients for plants when used as an organic fertilizer. This study aims to determine the effect of Gliricidia leaves liquid organic fertilizer on plant growth mustard and determine the concentration of gliricidia leaves liquid organic fertilizer optimally to enhance the growth of mustard. This research was conducted at the Biology Laboratory of Biology education studies program teacher training and Tarbiyah Faculty UIN Raden Fatah Palembang from May to June 2015, while for the analysis of gliricidia leaves liquid organic fertilizer held in the Research and Standardization Industry Palembang. This study uses a completely randomized design (RAL) with 4 treatments and 3 replications. Such treatment is 0 (K0), 40 (K1), 80 (K2), and 120 (K3) ml/l of water. The analysis showed that in the gliricidia leaves liquid organic fertilizer contained 0.24% N, 0.039% P, 8.38% K, 12.4% C-organic. Parameters measured were plant height, number of leaves, and leaf width. The research showed that the gliricidia leaves liquid organic fertilizer a significant influence on the growth of mustard. The concentration of 120 ml/l of water provide optimum influence on the growth of mustard